Subjectivity - Blackman, Lisa.; Walkerdine, Valerie; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan.)
Subjectivity is an international, transdisciplinary journal examining the social, cultural, historical and material processes, dynamics and structures of human experience. As topic, problem and resource, notions of subjectivity are relevant to many disciplines, including cultural studies, sociology, social theory, geography, anthropology and psychology. The journal brings together scholars from across the social sciences and the humanities, publishing high-quality theoretical and empirical papers that address the processes by which subjectivities are produced, explore subjectivity as a locus of social change, and examine how emerging subjectivities remake our social worlds.
Keywords: Social sciences; Social Sciences, general